1977
DOI: 10.1007/bf00688565
|View full text |Cite
|
Sign up to set email alerts
|

Atypical subacute sclerosing panencephalitis

Abstract: An unusual case of panencephalitis in a 4-year-old Japanese boy, with onset at three months after measles infection and rapid progression to a comatose state in approximately one month, is described. A rapid rise in serum measles antibody titre after the onset of the symptoms, and the appearance of various abnormal antibodies in the serum, were noted. Pathologically, the brain showed sclerosing polio- and leucoencephalitis with diffuse gliosis and sporadic intranuclear inclusions. The process is suggested to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

1978
1978
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…On the basis of our case and other recent reports (Lyon, 1972;Murphy and Yunis, 1976;Nihei et al, 1977;Wolinsky et al, 1977) it seems clear that this serious complication must be borne in mind during any form of cytotoxic treatment, immunosuppression, or immunodeficiency state lowering the resistance of the host to measles virus (Haltia et al, 1978). In our case we noted characteristic, rapidly progressive retinal changes, not reported by previous workers.…”
supporting
confidence: 78%
“…On the basis of our case and other recent reports (Lyon, 1972;Murphy and Yunis, 1976;Nihei et al, 1977;Wolinsky et al, 1977) it seems clear that this serious complication must be borne in mind during any form of cytotoxic treatment, immunosuppression, or immunodeficiency state lowering the resistance of the host to measles virus (Haltia et al, 1978). In our case we noted characteristic, rapidly progressive retinal changes, not reported by previous workers.…”
supporting
confidence: 78%
“…Cranial CT and/or head MRI were reported in 9 of these patients including ours (Cases 16,17,[20][21][22][23][24][25][26].12,18,19,21-24 All but one patient (Case 17)19 initially had apparently normal head CT scans; however, repeat studies in all revealed cerebral atrophy. Our patient had a normal-appearing head CT and MRI; however, these were obtained at an early stage of the disease.…”
Section: Discussionmentioning
confidence: 83%
“…Of those who died, the patient who survived the longest was the 3-year-old child (Case 15). 17 Acute SSPE is an uncommon disease with protean symptomatology. It should be included in the differential diagnosis of acute unexplained encephalopathic diseases.…”
Section: Discussionmentioning
confidence: 99%